2013
DOI: 10.1093/carcin/bgt087
|View full text |Cite
|
Sign up to set email alerts
|

Millepachine, a novel chalcone, induces G 2 /M arrest by inhibiting CDK1 activity and causing apoptosis via ROS-mitochondrial apoptotic pathway in human hepatocarcinoma cells in vitro and in vivo

Abstract: In this study, we reported millepachine (MIL), a novel chalcone compound for the first time isolated from Millettia pachycarpa Benth (Leguminosae), induced cell cycle arrest and apoptosis in human hepatocarcinoma cells in vitro and in vivo. In in vitro screening experiments, MIL showed strong antiproliferation activity in several human cancer cell lines, especially in HepG2 cells with an IC50 of 1.51 µM. Therefore, we chose HepG2 and SK-HEP-1 cells to study MIL's antitumor mechanism. Flow cytometry showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 40 publications
2
60
0
Order By: Relevance
“…Moreover, in several human cancers, the role of CDK1 has been well characterized. Some researchers observed that in breast, hepatocarcinoma, oral, and lung carcinomas, CDK1 was found to be upregulated and correlated with clinicopathological factors [9,[17][18][19]. Besides, CDK1 is required for the distant metastases of colon cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in several human cancers, the role of CDK1 has been well characterized. Some researchers observed that in breast, hepatocarcinoma, oral, and lung carcinomas, CDK1 was found to be upregulated and correlated with clinicopathological factors [9,[17][18][19]. Besides, CDK1 is required for the distant metastases of colon cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the CDK1-cyclin B brings the onset of mitosis and is tightly regulated. During G2 phase, CDK1-cyclin B complex is held in an inactive state by phosphorylation of CDK1 at the two negative regulatory sites (Lindqvist et al, 2007;Gavet et al, 2010;Wu et al, 2013). AHL significantly affected the expression of CyclinB1 and CDK1 proteins in HepG-2 cell, CyclinB1 proteins expression level in HepG-2 cells was unregulated upon the treatment of three concentrations of AHL (2.0μg/ml, 4.0μg/ml and 8.0µg/ml respectively) (p<0.01), Whereas, the CDK1 showed unregulated expression upon the treatment of moderate dose (4.0μg/ml ) and high dose (8.0μg/ml ) of AHL (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Cells (2 × 10 3 -1 × 10 4 cells per well) were seeded in 96-well culture plates overnight for attachment, then treated with vehicle alone or various concentrations of SKLB-M8 for 24 h (HUVECs) or 48 h (melanoma cells), and measured using the MTT assay with a Spectramax M5 Microtiter Plate Luminometer (Molecular Devices) as previously described (11). Each assay performed in triplicate.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Millepachine (MIL), a novel chalcone with a 2,2-dimethylbenzopyran motif, was first isolated from Millettia pachycarpa Benth (Leguminosae) by our group, which is a flavonoid-rich traditional Chinese medicine, has been used as a blood tonic in antihelminthic and cancer therapy for many years in China. In our previous studies, MIL was reported to be a potential lead compound for antitumor drug development and induced cell cycle arrest and apoptosis in human hepatocarcinoma cells (11). However, the poor solubility of MIL limited its further higher dose treatment.…”
Section: Introductionmentioning
confidence: 99%